BAS/BSCR27 Diesel exhaust particles promote atherosclerosis in apolipoprotein E-deficient mice. Issue 17 (26th August 2010) - Miller, M R; McLean, S G; Duffin, R; Shaw, C A; Mills, N L; Donaldson, K; Newby, D E; Hadoke, P W F
Abstract : Air pollution has been linked to the development of atherosclerosis and cardiovascular disease. Diesel exhaust particulate (DEP) accounts for a substantial proportion of urban air pollution but its effects on atherogenesis are unknown. We hypothesised that DEP will exacerbate plaque formation in a murine model of atherosclerosis. Apolipoprotein E knockout (ApoE) mice (10–12 weeks; n=16) were fed a 'Western diet' (21% cholesterol) for 8 weeks to induce the development of 'complex' atherosclerotic plaques. During the last 4 weeks of feeding, mice underwent twice-weekly intratracheal instillation of 35 μl DEP (1 mg/ml; National Institute of Standards and Technology) or vehicle (saline). Histological sections of the brachiocephalic artery from ApoE knockout mice showed large, foam cell-filled fibrous plaques. Plaque burden was increased (p=0.025; n=5–6) in DEP-treated mice (69±9%) compared with vehicle-treated controls (42±7%). Furthermore, plaques from DEP-treated mice exhibited a greater number of adjoining (2.3±0.2%) and buried (1.2±0.3%) fibrous caps than control mice (1.7±0.2% and 0.2±0.1%, respectively; p<0.05 n=5). There was no evidence of systemic inflammation, increased circulating blood lipids or endothelial dysfunction in DEP-treated animals. This is the first study to show that pulmonary exposure to the particulate matter within diesel exhaust enhances atherogenesis. This action may, therefore, contribute to the increased cardiovascular morbidity and mortality associated with air pollution. This model will allow identification of the constituents of DEP that mediate this atherogenic effect and provide an important insight into potential interventions to reduce the impact of vehicular emissions.